2015
DOI: 10.1108/bpmj-11-2013-0144
|View full text |Cite
|
Sign up to set email alerts
|

An activity-based costing approach for detecting inefficiencies of healthcare processes

Abstract: Purpose – The purpose of this paper is to set out a methodological framework to investigate how the integration of an activity-based costing (ABC) logic into the pre-existent accounting system supports healthcare organizations in identifying the inefficiencies related to their diagnostic therapeutic pathways (DTP) and related reengineering interventions. Design/methodology/approach – The BPM-ABC methodological framework has been applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 39 publications
(44 reference statements)
0
24
0
3
Order By: Relevance
“…It consists of three basic elements: Process Management, Cost Analysis using ABC, Balanced Scorecard. [9], [10], [11] argue that process management can affect the level of costs, profits, value added, and other attributes of the business's value-creation processes. The ABC method is the main tool.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It consists of three basic elements: Process Management, Cost Analysis using ABC, Balanced Scorecard. [9], [10], [11] argue that process management can affect the level of costs, profits, value added, and other attributes of the business's value-creation processes. The ABC method is the main tool.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have described the implementation of ABC in the health care sector, in clinics and hospitals . Other studies have shown that it is possible to use ABC to measure inefficiencies in care trajectories and, by applying business process reengineering, to identify inefficiencies in care trajectories in a hospital, integrating the logic of this method within an existing accounting system …”
Section: Introductionmentioning
confidence: 99%
“…It is also important to have complete staff buy‐in, and employees may be reluctant to implement the system . Moreover, it can be difficult to obtain information on activities from a system that focuses on cost centers . Finally, even if an organization succeeds in implementing an initial model, it must be constantly updated by questioning the stakeholders in the organization to make sure the model reflects any changes…”
Section: Introductionmentioning
confidence: 99%
“…Promover BPM habilita a organização a conhecer seus processos, o que pode auxiliar os gestores a redesenhar os fluxos de trabalho para torná-los mais eficientes e eficazes e para reduzir custos desnecessários (CANNAVACCIUOLO et al, 2015). BPM pode ainda, auxiliar na execução de um programa estratégico por permitir melhor adequação entre a estratégia organizacional e os processos de negócios da organização (TRKMAN, 2010).…”
Section: Business Process Management -Bpmunclassified